Measuring of Braking Distances of Firefighting Trucks - Ladislav Jánošík; Ivana Jánošíková; Jiří Kuczaj; Pavel Poledňák; Izabela Šudrychová; Martin Tomášek; Josef Vlček (Communications - Scientific letters of the University of Zilina, 2022)
The paper addresses the driving dynamics of emergency fire trucks. It focuses on the issues of braking, measuring real braking distances and calculating adhesion coefficients. It presents the results of measuring the real braking distances for firefighting vehicles - type water tenders. Measurements were taken on dry asphalt and depending on the vehicle’s speed of travel. Experiments were conducted on five types of firefighting vehicles. The results of measurements are mainly used by fire protection units to the drivers’ self-education to improve safety when driving to intervene.